Community of Disciples as a Model of Church - Dulles, Avery (Philosophy & theology, 1986)
Models of the Church (published 1974) still seems adequate as an overview of the dominant types of ecclesiology in our day. It leaves open the question whether a single model could be found to harmonize the differences among the five described. To this end the author later proposed “community of disciples.” Well grounded in the Gospels, this model relies also on the post-Easter concept of discipleship as inclusive of the whole Christian life. Christian catechesis, ministry, and sacraments can profitably be understood as means of fostering discipleship, which also demands missionary activity for its completion. The discipleship model is appropriate in an age of dechristianization, when the Church must necessarily assume the form of a contrast society. This model, however, needs to be appraised in the light of the other five, which in some ways supplement and correct it.